HUBUNGAN LAMA TERAPI HEMODIALISA DENGAN SKALA PRURITUS PASIEN GAGAL GINJAL KRONIS - Perwiraningtyas, Pertiwi -; Sutriningsih, Ani - (Universitas Tribhuwana Tunggadewi, 2021)
Patients with end-stage chronic renal failure required hemodialysis to survive for a long time. One of the complications of hemodialysis therapy is pruritus. Pruritus interfered with the patient's activities and sleep quality so that it has an impact on the quality of life. The purpose of this study was to determine the relationship between the length of hemodialysis therapy and pruritus in patients with chronic kidney failure. The research design is cross sectional. The population of all chronic kidney failure patients at Panti Waluya Hospital Malang during November 2020 who underwent hemodialysis was 56 people. Simple random sampling was used as the sampling technique, so that a sample of 45 people met the inclusion criteria. Analysis test with Mann Whitney, the result of the mean length of time patients undergoing hemodialysis is 2 years 5 months. The median score for patients with pruritus was 5 (moderate category – itching indicated frequent scratching). The results of the analysis test showed that there was a relationship between duration of hemodialysis and pruritus (p value = 0.033). Nurses in the hemodialysis room need to provide health education related to non-pharmacological management of pruritus as a result of hemodialysis therapy for patients with chronic renal failure. This is an effort to minimize the severity of pruritus that causes sleep disturbances so that it indirectly reduces the activity and quality of life of patients with chronic kidney failure. Keywords : Chronic renal failure, Hemodialysis, Pruritus